Experiment and simulation study of the effect of ethanol and compound additives on the urea-based selective non-catalytic reduction process under moderate temperature conditions. Issue 10 (24th October 2018) - Wu, Bang; Pu, Ge; Du, Jiantai
Abstract : An experiment and simulation study of the effect of using liquid additives on the selective non-catalytic reduction (SNCR) process is presented, providing a novel way for plants reducing NOX emissions. An experimental study is conducted in an entrained flow reactor, and CHEMKIN is applied for simulation study. Ethanol additive can effectively shift the temperature window of the NOX OUT process to a lower range and the NOX OUT efficiency ranges from 29 to 56% at 700–800°C. Furthermore, ethanol additive has a significant inhibitory effect on ammonia slip. Na2 SO4 and C2 H5 OH can be combined into a compound additive, which has a synergistic effect on NO reduction. The addition of methanol can greatly promote denitrification efficiency from 650°C to 725°C, indicating the potential of compound additives in NO reduction. The HNCO + OH = H2 O + NCO pathway is also proven to be enhanced for ethanol decomposition, thereby providing OH, which is active in NO reduction. Finally, the reaction routes for ethanol on the urea-based SNCR process at the proper temperature are proposed.